Ubiquitination-dependent mechanisms regulate synaptic growth and function. - DiAntonio, A.; Haghighi, A.P.; Portman, S.L.; Lee, J.D.; Amaranto, A.M.; Goodman, C.S. (Nature, 2001)
The covalent attachment of ubiquitin to cellular proteins is a powerful mechanism for controlling protein activity and localization. Ubiquitination is a reversible modification promoted by ubiquitin ligases and antagonized by deubiquitinating proteases. Ubiquitin-dependent mechanisms regulate many important processes including cell-cycle progression, apoptosis and transcriptional regulation. Here we show that ubiquitin-dependent mechanisms regulate synaptic development at the Drosophila neuromuscular junction (NMJ). Neuronal overexpression of the deubiquitinating protease fat facets leads to a profound disruption of synaptic growth control; there is a large increase in the number of synaptic boutons, an elaboration of the synaptic branching pattern, and a disruption of synaptic function. Antagonizing the ubiquitination pathway in neurons by expression of the yeast deubiquitinating protease UBP2 (ref. 5) also produces synaptic overgrowth and dysfunction. Genetic interactions between fat facets and highwire, a negative regulator of synaptic growth that has structural homology to a family of ubiquitin ligases, suggest that synaptic development may be controlled by the balance between positive and negative regulators of ubiquitination.